Improving the Effectiveness of Room Sales Accounting Information System at Hotels Near Araya Family Club House: Peningkatan Efektivitas Sistem Informasi Akuntansi Penjualan Kamar di Hotel Near Araya Family Club House - Sodik; Survival; Irfan Fatoni; Indah Dewi Nurhayati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Hotel Near Araya Family Club House faces challenges in managing its accounting information system for room sales, relying on manual record-keeping. This study aims to evaluate the implementation of a new accounting information system for room sales to improve efficiency, accuracy, and transparency. Using the Participatory Action Research (PAR) method, the service team collaborates with the hotel management to identify issues, plan solutions, and implement the new system. The results of the implementation show significant improvements in the speed of receiving reports and data accuracy, as well as a reduction in recording errors. The main challenge was the adaptation process of staff to the new system, which was addressed through intensive training. With the new system, decision-making is faster, financial report transparency is enhanced, and guest satisfaction is improved. A more efficient information system plays a crucial role in supporting better hotel operations and long-term business sustainability.